Palatalisation in Dublin Irish, or How to Speak Irish with a Dublin Accent - Snesareva, Marina (Studia Celtica Posnaniensia, 2017)
This paper focuses on palatalisation in Irish spoken by Dublin-based bilinguals with English as their first language. As opposed to previous researches in Irish phonetics and phonology, this study examines new speakers of Irish, whose speech was recorded in November 2014. All informants were born and raised in Dublin, lived either in the city or in the neighbouring counties and demonstrated sufficient fluency in Irish, i.e. had no problems with reading, could actively participate in conversation and give detailed answers without switching to English. Computer analysis of their data has shown that even though in traditional Irish dialects palatalisation is not position-bound, there is a correlation between palatalisation of a consonant and its neighbouring vowel quality in the speech of Dublin bilingualsdue to English influence andother factors.